Roles of Phytoestrogen in the Pathophysiology of Intracranial Aneurysm. Issue 8 (23rd June 2021) - Yokosuka, Kimihiko; Rutledge, Caleb; Kamio, Yoshinobu; Kuwabara, Atsushi; Sato, Hiroki; Rahmani, Redi; Purcell, James; Eguchi, Satoru; Baranoski, Jacob F.; Margaryan, Tigran; Tovmasyan, Artak; Ai, Jinglu; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: The incidences of intracranial aneurysm and aneurysmal subarachnoid hemorrhage are high in postmenopausal women. Although population-based studies suggest that hormone replacement therapy is beneficial for postmenopausal women with intracranial aneurysms, estrogen replacement may no longer be recommended for the prevention of chronic diseases given its association with adverse outcomes, such as cancer and ischemic stroke. The isoflavone daidzein and its intestinal metabolite equol are bioactive phytoestrogens and potent agonists of estrogen receptors. Given their estrogenic properties, we investigated whether the isoflavones daidzein and equol are protective against the formation and rupture of intracranial aneurysms in a mouse model of the postmenopausal state. Methods: We induced intracranial aneurysms in ovariectomized adult female mice using a combination of induced systemic hypertension and a single injection of elastase into the cerebrospinal fluid. We fed the mice with an isoflavone-free diet with/without daidzein supplementation, or in a combination of intraperitoneal equol, or oral vancomycin treatment. We also used estrogen receptor beta knockout mice. Results: Both dietary daidzein and supplementation with its metabolite, equol, were protective against aneurysm formation in ovariectomized mice. The protective effects of daidzein and equol required estrogen receptor-β. The disruption of the intestinal microbial conversion of daidzein to equol abolished daidzein's protective effect against aneurysm formation. Mice treated with equol had lower inflammatory cytokines in the cerebral arteries, suggesting that phytoestrogens modulate inflammatory processes important to intracranial aneurysm pathogenesis. Conclusions: Our study establishes that both dietary daidzein and its metabolite, equol, protect against aneurysm formation in ovariectomized female mice through the activation of estrogen receptor-β and subsequent suppression of inflammation. Dietary daidzein's protective effect required the intestinal conversion to equol. Our results indicate the potential therapeutic value of dietary daidzein and its metabolite, equol, for the prevention of the formation of intracranial aneurysms and related subarachnoid hemorrhage.